The Role of Type 2 Innate Lymphoid Cells in Adenoid Hypertrophy with Allergic Rhinitis Among Children and Related Potential Therapeutic Targets - Hao Y; Hu TY; Zhao MZ; Zeng XH; Li K; Cheng BH; Liu DB (Journal of Inflammation Research)
Yan Hao,1– 3 Tian-Yong Hu,3 Mei-Zhen Zhao,3 Xian-Hai Zeng,3 Ke Li,3 Bao-Hui Cheng,3 Da-Bo Liu1,2 1Department of Pediatric Otolaryngology, Shenzhen Hospital, Southern Medical University, Shenzhen, People’s Republic of China; 2The Third School of Clinical Medicine, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Otolaryngology, Shenzhen Longgang Otolaryngology Hospital & Shenzhen Otolaryngology Research Institute, Shenzhen, People’s Republic of ChinaCorrespondence: Bao-Hui Cheng, Email chengbaohui@sina.com Da-Bo Liu, Email daboliu@mailnesia.comObjective: Innate lymphoid cells (ILC) are a heterogeneous group of immune cells implicated in immune diseases. However, their specific roles in adenoid hypertrophy (AH), AH with allergic rhinitis (AH+AR), and AH with otitis media with effusion (AH+OME) remain poorly understood. This study aimed to characterize ILC subsets and their association with immunological profiles in these conditions.Methods: Flow cytometry was used to quantify ILC subsets in adenoid tissues from patients with AH, AH+AR, or AH+OME, and correlations between ILC subsets and clinical, immunological (serum and tissue cytokines), and histopathological parameters were further assessed.Results: ST2 mRNA and protein expression were significantly higher in AH+AR than in AH and AH+OME (p < 0.05). Serum IL-33 was elevated in AH+AR compared to AH (p = 0.0127), while IFN-γ was higher in AH than in AH+AR (p = 0.0044). IL-4 levels were higher in AH and AH+AR than in AH+OME (p < 0.005). Flow cytometry showed that ILC2 predominated in AH+AR (p = 0.0009 vs AH+OME), with higher ILC2/ILC1 and ILC2/ILC3 ratios in AH and AH+AR compared to AH+OME (p < 0.05). Correlation analysis indicated that ILC2 in AH+AR positively correlated with serum IgE, IL-4, IL-33, thymic stromal lymphopoietin (TSLP), and tissue IL-4, IL-33, TSLP, and IL-25 (p < 0.05). ILC3 inversely correlated with peripheral blood eosinophils (p = 0.0125) and positively with serum and tissue IL-17A (p < 0.05).Conclusion: ILC2 cells are significantly enriched in adenoid tissues of patients with AH+AR, with elevated ST2 and IL-33 levels supporting the activation of the IL-33/ST2/ILC2 signaling pathway. Targeting this pathway may offer novel therapeutic strategies for AH combined with allergic rhinitis.Keywords: adenoid hypertrophy, innate lymphoid cells, allergic rhinitis, otitis media with effusion, group 2 innate lymphoid cell